Knowledge internalization in e-learning management system - Zahraa Abed Aljasim Muhisn; Mazida Ahmad; Mazni Omar; Sinan Adnan Muhisn (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Knowledge management (KM) is gaining significance as a worthy research subject due to its contribution to the success of wide range of organizations, including higher education institutions. Knowledge internalization is mainly related to capability to see the relevance of one’s knowledge in a real situation. e-learning management system (eLMS) provides an online teaching and learning platform for students (as novice users) and lecturers (as experts in their specific domains) with the potential to improve students' knowledge acquisition. Thus, this empirical study was conducted to investigate the impact of knowledge internalization in eLMS among students in Iraq. To achieve these aims, survey research design was adopted and the sample comprised of 109 undergraduate students attending College of Information Technology in Iraq, all of whom were actively engaged in eLMS activities. The findings show that knowledge can be effectively transferred from lecturers to students via eLMS. Additionally, eLMS enable students to improve their prior knowledge through the internalization process, while also motivating them to share their knowledge with other students.